Restoration of the Greek Catholic Church in Czechoslovakia During the Prague Spring - Hromják, Ľuboslav (Religions, 2025)
The Greek Catholic Church in Czechoslovakia found itself outlawed after its violent liquidation by the brachial communist power in 1950, and the members of this church were forced to convert to the Orthodox faith. This study explains the difficult process of renewal of the Greek Catholic Church and its structures in the context of the Ostpolitik of the Holy See, represented by the Vatican diplomat and later secretary of state Agostino Casaroli, and in the context of the political relaxation in Czechoslovakia in 1968, during the so-called Prague Spring. In addition to the scientific literature, this study is based on historical research carried out in the historical archive of the Secretariat of State in the Vatican within the Agostino Casaroli fund, which has so far been processed little. In the study, the author describes the most significant steps which lead to the official legalization of the Greek Catholic Church on June 13, 1968, as well as the difficult process of negotiating the terms of the restored church with the state-enforced Orthodox Church.